A Facile Synthesis and Thermal Stability of cis-[Pd(NH3)2(C2O4)] - Xia, Wenzheng; Pan, Zaifu; Chen, Jialin; Ye, Qingsong; Liu, Weiping (Asian Journal of Chemistry, 2010)
A simple and facile method for synthesis of cis-[Pd(NH3)2(C2O4)] has been developed and the thermal decomposition behaviour investigated with TG-DTA under air and nitrogen atmosphere. The complex was prepared by the direct reaction of palladium chloride with ammonium oxalate at mild temperature and the yield was up to 76 %. cis-[Pd(NH3)2(C2O4)] undergoes the thermal decomposition, respectively, at 180 ºC in air and 172 ºC in N2, leading to the formation of Pd powder and CO2 and NH3 as the gas products.